Emotional Distress Among Suicide Survivors: The Moderating Role of Self-Forgiveness - Levi-Belz, Yossi; Gilo, Tal (Frontiers in Psychiatry, 2020)
Grief after suicide entails unique challenges and difficulties, such as intense feelings of anger and guilt, as well as various psychological risks. The current study examined the contribution of self-forgiveness (SF) to emotional distress (e.g., depressed mood and suicidal ideation) among suicide-loss survivors, compared with bereavement following sudden and expected death types. Bereaved individuals (N = 309; aged 18-84) completed questionnaires measuring SF, depressed mood, suicidal ideation, demographics, and personal characteristics concerning the bereavement. A significant interaction between SF and type of loss was found, in which suicide-loss survivors with low levels of SF manifested the highest levels of depression and suicidal ideation compared with other subgroups. The findings reflect the importance of SF as a protective factor against depression and suicidality among suicide-loss survivors as well as the possible efficacy of forgiveness-based interventions in this population.